Barriers to Inclusion: Exploring the Root Causes of Inclusive Education Challenges in Indonesia - Dian Isnawati; Rinny Apriliany Zakaria; Laurensia Claudia Pratomo (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to identify the inhibiting factors in the implementation of inclusive education in Indonesia. Using a qualitative approach through literature review and supported by interviews, the research reveals five key barriers affecting the effectiveness of inclusive education: (1) limited teacher competence and educational personnel, (2) insufficient infrastructure and support facilities, (3) social stigma and negative public attitudes towards children with special needs (CWSN), (4) institutional unpreparedness, and (5) socioeconomic inequality and uneven distribution of inclusive schools. The findings highlight that the success of inclusive education depends on synergy between policies, institutional readiness, and societal attitude shifts. The study recommends continuous teacher training, improved educational infrastructure, and public awareness campaigns to support a more inclusive education system in the future.